2018
DOI: 10.1021/acs.iecr.8b02735
|View full text |Cite
|
Sign up to set email alerts
|

Gas Transport Properties in Cross-Linked and Vacuum Annealed Poly(oxyindole biphenylylene) Membranes

Abstract: This work studies useful routes to produce cross-linked poly(oxyindole biphenylylene) bearing a crosslinkable propargyl group, PNPr. Thus, the effect of crosslinking temperature and time on gas permeability and ideal selectivity for a non-cross-linked PNPr membrane to produce a cross-linked PNPr membrane is studied in detail in order to learn how more productive membranes, in terms of permeability−selectivity combinations, and membranes resistant to solvent swelling and CO 2 plasticization may be produced. Sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
2
5
0
1
Order By: Relevance
“…Their high thermal resistances allow the POXINARs to be termed highperformance polymers, and this is an important property for many polymer applications and for further postmodifications (e.g., thermal cross-linking throughout propargyl groups, as has been reported elsewhere). 9,10 The experimental specific volumes and FFVs are comparable to those reported for the well-known polysulfone, 20 polycarbonate, 21,22 and polyarylate 23 families. The chemical structural changes in the repeating units of the polymers affect their packing densities as estimated from FFV.…”
Section: Methodssupporting
confidence: 76%
See 1 more Smart Citation
“…Their high thermal resistances allow the POXINARs to be termed highperformance polymers, and this is an important property for many polymer applications and for further postmodifications (e.g., thermal cross-linking throughout propargyl groups, as has been reported elsewhere). 9,10 The experimental specific volumes and FFVs are comparable to those reported for the well-known polysulfone, 20 polycarbonate, 21,22 and polyarylate 23 families. The chemical structural changes in the repeating units of the polymers affect their packing densities as estimated from FFV.…”
Section: Methodssupporting
confidence: 76%
“…More recently, polymer 2aA was used as a model for incorporating thermolabile and cross-linkable groups to illustrate how different thermal treatments lead to POXINAR membranes that not only possess attractive gas permeability and selectivity properties but also are more resistant to aggressive solvents and aging . An unusual and very interesting example of thermal cross-linking of a 2aA membrane followed by long-term annealing under vacuum (10 –3 Torr) was reported; the resulting polymers were resistant to solvent swelling and CO 2 plasticization up to 18 bar, and the selectivity–permeability combinations for O 2 /N 2 overcome the typical trade-off between permeability and selectivity, falling above Robeson’s 2008 upper-bound limit.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the developed polymeric membranes and MMMs did not display a clear tendency to fracture; this is mainly due to its high thermostability with no significant weight loss below 500 °C (under air) as observed in thermogravimetric analysis (TGA) studies (Figure and Table S1), and glass-transition temperatures were not detected before its decomposition temperature. This behavior is analogous to that of similar polymers. , On the other hand, the obtained MMMs withstood harsh conditions during solvent evaporation (up to 200 °C, when NMP was used as a solvent) and gas transport measurements where pressures up to 2 bar were employed. This depicts the good thermal and mechanical stabilities, at least under the conditions studied, of the obtained MMMs.…”
Section: Resultssupporting
confidence: 62%
“…It has also been shown that it is possible to modify the isatin moiety to obtain polymers with different pendant groups. 18,19 Several reports show that these highly aromatic polymers have glass transition temperatures, T g values, above 400 °C and onset of decomposition temperature, T d , above 450 °C. Furthermore, given their highly aromatic structure they present a high residual char around 75% at 800 °C.…”
Section: Introductionmentioning
confidence: 99%